Reduced CD200 expression is associated with altered Th1/Th2 cytokine production in placental trophoblasts from preeclampsia. (20th September 2017) - Xu, Jie; Gu, Yang; Sun, Jingxia; Zhu, Hui; Lewis, David F.; Wang, Yuping
Abstract : Problem: To determine if altered trophoblast CD200 and CD200R expressions promote inflammatory cytokine production in preeclamptic placentas. Methods of study: Placental tissue CD200 and CD200R expressions were determined by immunostaining. Tissue sections from first‐, second‐, and third‐trimester, normal term, and preeclamptic placentas were used. CD200 and CD200R expressions and cytokine production of TNFα, sTNFR1, INFγ, IL‐4, IL‐6, IL‐8, and IL‐10 were determined in trophoblasts from normal and preeclamptic placentas and in normal trophoblasts transfected with CD200 siRNA. Results: CD200, but not CD200R, expression was significantly reduced in trophoblasts from preeclamptic compared to normal placentas. Trophoblast from preeclamptic placentas and trophoblast transfected with CD200 siRNA produced significantly more TNFα, sTNFR1, IL‐6, and IL‐8, but significantly less IL‐10, than trophoblasts from normal control placentas. Conclusion: Downregulation of CD200 expression resulted in an imbalance of increased Th1 cytokine and decreased Th2 cytokine production in placental trophoblasts in preeclampsia.